(untitled) (TEST Ticontre. Theory Text Translation, 2018)
Based on Alison Bechdel’s autobiographical essay Are You My Mother?, this article is a discussion on two boundaries of the essay : a generic boundary between essay and autobiography, questioned by the possibility of autobiographical essay, and an intermedial boundary challenged by the development of graphic essays in comics. Are You My Mother? is a self-reflexive autobiographical work which describes the author’s discovery of psychoanalysis and deals at the same time with mother-child relationships and the continuity between novel writing, autobiography and psychoanalysis, thus articulating autobiographical material and general thoughts. The book can be described in particular as a consistent dialogue with Donald Winnicott’s work, which we can see through the profusion of panels entirely devoted to quotes or the association of each chapter title to one of his articles. The boundary between essay and autobiography is embodied in the specificities of the medium, in particular its sequential mode, usually associated with narrative, and text / image relations. Alison Bechdel frequently breaks narrative sequentiality and uses parallel progressions of recitatives and iconic sequences to confront her experience and theoretical concepts, disrupting in the process any simple correspondence by multiplying narratives and fictional or real characters.